The study of human language in human life - R. H. Robins (Journal of Modern Languages)
Linguistics is quite simply the scientific study of human language in all its manifestations and uses, near and far, past and present, without restriction on time, place, or culture. In this respect linguistics is different from language study, since this latter terrm is normally used to refer to the study of a particular language, say Latin, French, German, Malay, or English, in order to read its literature in the original language, or for the purposes of written or spoken communication with its speakers.